TRILHANDO CAMINHOS DE EMANCIPAÇÃO: O MOVIMENTO DE MULHERES NEGRAS FACE AO AVANÇO DO NEOCONSERVADORISMO - Guedes, Bruna Menezes (2022)
This research has as main objective to rescue the process of organization of the Black Women's March in Brazil and to analyze the proposed demands by the March against the advance of neoconservatism in Brazil, in view of the contradiction in the face of the limits and possibilities of achievements and setbacks in government agendas that address the claims of black women. To this end, we approach the racial debate in the context of Brazilian social thought, along with the implications of patriarchy and intertwining in the end the participation of black women in politics with an emphasis on national meetings of black women. Following, we approach the articulation between the vindication of social movements of black women in front of the current governments, resulting at a first moment, in institutional achievements such as the constitution of the SPM and SEPPIR, we also point out the obstacles faced by the secretariats and, at the end, we raised the debate about neoconservatism in Brazil. Finally, we present the Articulation of Black Women's Organizations as a fundamental movement for the organization of the Black Women's March, as well as the actions developed by black women's movements since their formal organization, which extends to the pandemic period. For that, we adopted bibliographic and documentary research (based on digital sources and personal collection), seeking to rely on the dialectical historical materialist method. Finally, we conclude that the March consists of the realization of an organized act of black women's movements that continue in the daily struggle and resistance in their territories, in this way, black women were and are uninterruptedly on the march.